Reflections of a Black Male Counseling Psychology Doctoral Student: Lessons Learned from APA Division 45 Commentary and the Role of Social Justice for Counseling Psychologists - Ricky J. Pope, M.A. (Journal for Social Action in Counseling and Psychology)
The tragic killing of Trayvon Martin has received nationwide media coverage, even garnering commentary by the U.S. President. The attention is unique in the sense that young Black men in Martin’s age group have consistently been the most likely to be killed as a result of homicide and often ignored by the media. A personal reflection is provided to give context to the racial socialization process as well as the internal struggles being faced by some Black men in the United States. In addition, postings have been shared from the American Psychological Association Division 45 electronic mailing list capturing the social justice activism process in pursuit of justice for Trayvon Martin. The results of this article call for deeper analysis of the cause of racially motivated killings.